34.1: Invited Paper: Effect of Singlet Triplet Recycling in the Charge Transfer State Manifold and Molecular Geometry on Thermally Activated Delayed Fluorescence. Issue 1 (June 2015) - Dias, Fernando B.; Graves, David; Jankus, Vygintas; Monkman, Andrew P.
Abstract : Detailed photophysical measurements of intramolecular charge transfer states have been made both in solution and solid state. Temperature dependent emission and delayed emission are used to map the energy levels involved in molecule decay, and through detailed kinetic modeling of the thermally activated processes observed, true electron exchange energies, and energy barrier for reverse intersystem crossing of the systems determined. From this it is possible to simply determine many rate constants for the TADF mechanism and the magnitude of triplet contribution to overall emission.